Class II malocclusion treatment using Jasper Jumper appliance associated to intermaxillary elastics: a case report - Francyle Simões Herrera-Sanches; José Fernando Castanha Henriques; Guilherme Janson; Leniana Santos Neves; Karina Jerônimo Rodrigues Santiago de Lima; Rafael Pinelli Henriques; Lucelma Vilela Pieri (Dental Press Editora, 2013)
INTRODUCTION: Skeletal, dental and profile discrepancies can be amended by using functional orthodontic appliances. OBJECTIVE: This study is a report of the treatment of a patient, 11 years and 4 months old, with Class II, division 1, malocclusion, convex profile, protrusion of upper incisors, pronounced overjet and overbite, and mild crowding. METHODS: The patient was treated with a Jasper Jumper associated to fixed appliances for 6 months and Class II intermaxillary elastics (3/16in) during the last 4 months. After debonding, a Hawley retainer was used during daytime and a modified Bionator for night use during one year. In the lower dental arch a bonded lingual retainer was used. This treatment combination improved the profile, as well as the overjet, overbite and molar relation. RESULTS: There was clockwise mandibular rotation and increase of lower anterior facial height. The lower incisors were protruded and extruded and the lower molars were extruded. The centric occlusal relation was checked and it was coincident to the maximum usual intercuspation. CONCLUSION: It was demonstrated that the Jasper Jumper is an efficient alternative to Class II malocclusion treatment, providing improvement in the facial profile, although the changes are more dentoalveolar than skeletal.